AN AUDIT ANALYSIS ON SERVICE INFORMATION SYSTEM AT ACADEMIC ADMINISTRATION BUREAU OF INFORMATICS AND BUSINESS INSTITUTE DARMAJAYA BANDAR LAMPUNG THROUGH COBIT 4.1 - Amnah - - (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Academic Administration Bureau is a bureau considered asstandards for giving service to all students of Informaticsand Business Institute Darmajaya (IBI Darmajaya).Information system at this bureau plays an important rolein providing service to the students and is expected to beable to improve job performance and service quality. Forthe time being the implemented service information systemat Academic Administration Bureau has not been muchbenefited and not known whether it is in accordance withthe vision and mission of the institution.To make the service offered by the academicadministration bureau relevant to the business goal of theinstitution, it is required to know the conformity levelbetween TI goal and Institutional goal. To obtain theconformity level between TI goal and institutional goal, itneeds a measurement of conformity level between the twogoals by using COBIT 4.1.The result finding of the research is the conformity levelbetween TI goal and institutional goal is obtained andstands at Defined level because the average of TI processeshas been above the international level standard as 2.5(Guldentops, 2000). Even though the average of TIprocesses has been over the international level standard,there are still some TI processes below the internationalstandard, so it requires recommendation to increase theconformity between TI goal and institutional goal to reacha higher level.KEY WORDS: Maturity level, Expected, InformationSystem, Asset Management, COBIT